DESIGN OF SALMON STORAGE PACKAGING TO MAINTAIN QUALITY USING THE QUALITY FUNCTION DEPLOYMENT (QFD) METHOD AND MORPHOLOGICAL CHART - Lidya Wijaya; Riko Kanady; Indira Ruth Septarini (RADJA PUBLIKA, 2026)
Salmon is a high-value food commodity that is highly susceptible to quality deterioration due to lipid oxidation and microbial growth during storage. This issue is often caused by packaging designs that do not fully accommodate product characteristics and consumer requirements. This study aims to develop a salmon packaging design capable of maintaining product quality and extending shelf life by integrating the Quality Function Deployment (QFD) method and the Morphological Chart approach. The theoretical framework and literature review cover food packaging concepts, QFD, the House of Quality, and the Morphological Chart as a tool for generating design alternatives. This research employs a descriptive method with qualitative and quantitative approaches. Data were collected through literature studies and the identification of the voice of customer, which were subsequently analyzed using QFD to determine priority technical requirements. The results indicate that packaging methods (vacuum/MAP), oxygen permeability, and storage temperature are the most critical technical priorities. Furthermore, the Morphological Chart produced an optimal design combination consisting of MAP packaging with very low oxygen control, multilayer food-grade materials, high sealing strength, and storage temperatures ranging from −1 to 0 °C. In conclusion, the integration of QFD and the Morphological Chart is effective in generating a salmon packaging design that meets consumer needs and preserves product quality.